Yield in chemical reactor engineering - 422295 Carberry, James J.
The industrialist is more concerned with product yield thyan with reactant conversion. Though yield is more important, much of the literature is written in terms of conversion, causing frequent distress to designers. The author reviews the situation in depth and provides criteria for simplying the designer's task.